AI-POWERED SCAFFOLDING: RETHINKING ENGLISH LANGUAGE TEACHING PRACTICES IN THE DIGITAL AGE - Jalaluddin Jalaluddin; Aamal Alfaqih; Yuxin Zhong (GLOBAL: Education Language and Humanity Journal, 2025)
The integration of artificial intelligence (AI) in English Language Teaching (ELT) presents new opportunities for personalized and adaptive instructional scaffolding. AI-powered tools such as intelligent tutoring systems, chatbots, and adaptive platforms offer real-time feedback, automated assessments, and context-aware support, redefining traditional pedagogical approaches. While the technical capabilities of AI have been widely studied, its pedagogical applications in scaffolding remain underexplored, particularly in relation to complex language skills and learner diversity. This paper addresses this gap by examining how AI-driven scaffolding can support learners at various stages of language acquisition. It explores theoretical foundations, practical implementations, and key technologies facilitating tailored learner support. Additionally, it evaluates ethical challenges, including data privacy, algorithmic bias, and the balance between AI and human facilitation. Finally, the paper offers recommendations for educators, researchers, and policymakers to maximize the pedagogical potential of AI in ELT.